Malaysian Private Education Quality: Application of SERVQUAL Model - Vaz, Anthony; Mansori, Shaheen (Canadian Center of Science and Education, 2013)
Intense competition among existing private education providers and the Malaysian government’s relaxation of regulations for allowing international universities to open off shore campuses in Malaysia, have forced companies in the education industry to develop strategies which can help them to make their existing students satisfied and keep them loyal to the brand. This paper, studied the impact of five factors of service quality (responsiveness, reliability, empathy, assurance, tangibility) on students’ satisfaction at private universities and colleges. For this purpose 431 questionnaires were collected from different private education providers in Malaysia. The results indicated that tangibility has an influence on satisfaction followed by empathy; responsiveness and assurance have a direct and positive effect on students’ satisfaction. However, reliability has not shown any impact of students’ satisfaction.